The politics of moral giving - Eyigünlü, Melek (Graduate School, 2023)
We are living in an era of increased income inequalities one that creates powerful moral-giving actors who take the role of decision-makers in the public realm. Over the centuries, the idea of moral giving has been associated with virtue as a character trait, human love, gift-giving, duties of beneficence, alms-giving, a utilitarian duty, an agent-sacrificing or an egoistic agent-favouring sense –a list that could be extended. Moral giving is a neologism deployed here as an umbrella term to include charity, philanthropy, benevolence, volunteerism and such like. It has been a topic in moral philosophy for centuries, but its political aspects have not been adequately studied and equally it refers to a topic that has been addressed in terms of its contemporary political aspects yet without a good philosophical and sociological grounding. Accordingly, this dissertation examines the complex ethical, social and political motives from different theoretical perspectives. The main research question is: What are the grounds that make moral giving a means to political ends? The main thesis is that moral giving is instrumentalized in the political field unless it is treated as end-in-itself – in other words, unless it is done for its own sake. In this context, 'instrumentalization' means using moral giving as a means for non-moral or immoral purpose. This thesis argues against dominant utilitarian perspectives and claims that the political instrumentalization of moral giving is not morally worthy as an act. Therefore, this work opposes instrumental moral giving, which means making giving valuable for the sake of something else and so an outcome-oriented moral giving. Accordingly, the main argument asserts that certain ethical positions and societal motivations support the instrumentalization of moral giving. Therefore, they also serve to make the act of giving a potential instrument of political functions. Consequently, this dissertation points out that that politicization of moral giving does not only stem from political motivations. Thus, this dissertation points out that that politicization of moral giving does not only stem from political motivations. The argumentation in this thesis has a complex structure. Therefore, as deemed necessary to first give descriptions of current, existing moral, social and political motives in order to better understand the ideal world asserted here There is one unique exception to the rejection of (social and political) motives that makes moral giving a means to another end. This concerns 'social justice', which is the subject of the last part (on the political aspect). That is, there is one and only end (justice) that can justify moral giving as a means to another end and thus asserts its value as extrinsic. Therefore, moral giving is both an end in itself and a means for social justice, which is intrinsically itself an end of moral giving. Finally, as it is not the ideal world in which moral giving is necessarily an end in itself, in the existing situation, there are complex and overlapping moral, social and political goals that motivate moral-giving actions. Moreover, it is difficult to identify and disentangle a giver's intertwined motivations. However, this should not prevent us from achieving a (morally) ideal political theory. In order to overview the motives and functions from different perspectives, this dissertation is built on three main parts: the ethical, social and political aspects. Following the introduction and the main driving motives of studying this subject, the first body part (Part 3), "The Ethical Aspect of Moral Giving" covers the main moral motives behind giving acts and outlines the principle arguments in the major theoretical approaches, listed as two main types: duty ethics and consequentialism. Here, under the duty perspective, the deontological, pluralist and natural law approaches are considered, while under the consequentialist perspective, the approaches of utilitarianism, virtue ethics, altruism and ethical egoism are argued. This part ends with the submission of an ideal synthesis developing a hybrid moral model that embraces specific points from the Kantian deontology and Aristotelian virtue ethics – mainly pointing us giving acts should not be conditional or performed for an ulterior motive, in other words should be fundamentally an end in itself. Finally, ethical part submits a theoretical guiding framework with which to examine the social and political functions that moral giving plays and the moral limits to which it should adhere. The second body part, "The Social Aspect of Moral Giving" comprises two chapters, first one addresses questions in the methodological debate of the micro-macro dichotomy from an integrative perspective and then considers the social functions. The main aim is to analyse the social motivations behind moral-giving acts from different sociological perspectives, presenting, as the main argument, the idea that the social motivations, depending on their particular contexts -but within the whole of their interrelated motives-, that drive giving acts should be analysed from an integrative perspective that overcomes micro-macro dichotomy.
Ahlaki hayırseverliğin siyaseti
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: charity organizations; hayır kuruluşları; philantropy; hayırseverlik